2022
DOI: 10.1002/ece3.8470
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomics analysis reveals how the diet shapes the gut microbiota in several small mammals

Abstract: The gut microbiomes of the host are large and complex communities, which helps to maintain homeostasis, improves digestive efficiency, and promotes the development of the immune system. The small mammals distributed in Sichuan Province are the most popular species for biodiversity research in Southwest China. However, the effects of different diets on the structure and function of the gut microbial community of these small mammals are poorly understood. In this study, whole‐metagenome shotgun sequencing has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Studies have shown that Firmicutes have a higher efficiency of sugar metabolism than the Bacteroidetes , which favors energy absorption and promotes obesity [ 42 ]. A higher F/B ratio implies more energy intake and the possibility of being overweight [ 43 ]. The relationship between an increase or decrease in the F/B ratio and obesity is subject-dependent, and one study showed that: treatment of obese mice with Eurotium cristatum decreased the F/B ratio; similarly, treatment of obese dogs with Eurotium cristatum increased the F/B ratio [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that Firmicutes have a higher efficiency of sugar metabolism than the Bacteroidetes , which favors energy absorption and promotes obesity [ 42 ]. A higher F/B ratio implies more energy intake and the possibility of being overweight [ 43 ]. The relationship between an increase or decrease in the F/B ratio and obesity is subject-dependent, and one study showed that: treatment of obese mice with Eurotium cristatum decreased the F/B ratio; similarly, treatment of obese dogs with Eurotium cristatum increased the F/B ratio [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia belongs to the Verrucomicrobia family [ 57 ] and has been shown to reduce systemic disease LPS levels, weight gain, and fat mass in HFD-fed rats [ 58 ]. Numerous studies have shown that dietary polyphenols or flavonoids can promote the enrichment of Akkermansia in the intestines of mice [ 32 , 43 ]. In this study, the abundance of Akkermansia in the HD group was 58.4% higher than that in the MC group (0.0391) ( Figure 8 B), indicating that high-dose RFV contributed to the enrichment of Akkermansia in the intestine of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that biomarkers act as quantifiable indicators of a biological condition or exposure to the environment [ 36 ]. Genera such as Bacteroides / Prevotella and Bifidobacterium may be useful in this regard as indicators of food- and lifestyle change post-surgery [ 37 , 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…The increase of interest in the effects of intestinal microbiota on human health has led to extensive metagenome sequencing efforts to understand the variation and diversity between organisms and health conditions (40)(41)(42)(43) and the generation of preclinical models to elucidate the gut microbiome mechanism of action (44)(45)(46). The use of GF mice as the basis of the bidirectional gut microbiome-brain communication provides the opportunity to decipher the role of the gut microbiota and regulation of brain development and function.…”
Section: Discussionmentioning
confidence: 99%